Total Quality Control (TQC) Analysis of Paris Hijab Products at the Wholesale Center of Dodolan Hijab Surabaya Using Six Sigma, New Seven Tools and Kaizen Methods - Nugraha, Isna; Kirana, Intania Widyantari; Ramadhan, Gilang; Aryanti, Friska (2477 - 6165, 2025)
Dodolan Hijab is a hijab shop located on Jl. Medayu Utara Gg. VIII A No.19, Medokan Ayu, Surabaya. This shop offers various types of hijab, with Hijab Paris being one of the most popular and in-demand products. However, for some time, there has been a significant problem related to the high level of damage to Hijab Paris products, which includes 33% torn hijabs, 35% slanted cuts, and 32% pulled threads. This study aims to identify the types of defects that cause the high defect rate in Hijab Paris products over 12 month, as well as to analyze the factors that affect their quality. For this reason, the Six Sigma, New Seven Tools, and Kaizen approaches were applied to analyze the root cause and provide improvement solutions. Of the 11,745 hijabs produced, 281 units were found to be damaged. The results of the study showed that torn hijab defects were a top priority to be repaired in order to improve overall product quality. The suggested improvements were expected to make the production process more efficient, enhance the quality of Paris hijab products, and ultimately increase customer satisfaction.